Iridium(Nhc)-catalyzed sustainable transfer hydrogenation of co2 and inorganic carbonates - Cheong, Yeon Joo; Sung, Kihyuk; Kim, Jin A.; Kim, Yu Kwon; Yoon, Woojin; Yun, Hoseop; Jang, Hye Young (Catalysts, 2021)
Iridium(NHC)-catalyzed transfer hydrogenation (TH) of CO2 and inorganic carbonates with glycerol were conducted, demonstrating excellent turnover numbers (TONs) and turnover frequencies (TOFs) for the formation of formate and lactate. Regardless of carbon sources, excellent TOFs of formate were observed (CO2: 10,000 h−1 and K2CO3: 10,150 h−1). Iridium catalysts modified with the triscarbene ligand showed excellent catalytic activity at 200◦C and are a suitable choice for this transformation which requires a high temperature for high TONs of formate. On the basis of the control experiments, the transfer hydrogenation mechanism of CO2 was proposed.
Keywords: Carbon dioxide; Inorganic carbonate; Iridium(NHC); Transfer hydrogenation